Do You Do as I Do?: Young Toddlers Prefer and Copy Toy Choices of Similarly Acting Others. (17th March 2016) - Gerson, Sarah A.; Bekkering, Harold; Hunnius, Sabine
Abstract : Recognizing similarity between one's own and others' actions is important for identifying others with whom to affiliate and from whom to learn. In this study, 40 19‐month‐old toddlers recognized when a puppet chose the same toys as them. Toddlers preferred to affiliate with a puppet who chose the same toys as themselves relative to a puppet who chose other toys and they modified their subsequent behavior by choosing the same toys as that puppet when presented with novel toys. Toddlers' actions were not based on perceivable features of the puppet (e.g., similar accent or language as oneself) or an association between the puppet and the preferred toys (as assessed in a control condition). Results indicate that toddlers identified and recognized the similarity in action choices between themselves and the puppet via comparison between their own and the puppets' actions. Identifying this similarity is critical for children's developing understanding of and engagement in interactions with others.